Effectiveness of Yoga Nidra in reducing stress in school going adolescents: An experimental study. (November 2021) - D'souza, Ovine Loyster; Jose, Agnes Elizabeth; Suresh, Sucharitha; Baliga, Manjeshwar Shrinath
Abstract: Background and objectives: Academic stress can exert severe stress in adolescents answering their career deciding board exams. The present study attempted to understand the efficacy of Yoga Nidra (YN) in mitigating psychosocial stress. Design: and Methods: This study was carried on 10th-grade students (ages 14 to 16) and had two arms, one performing YN (experimental) and the other without YN (control) for 21 consecutive days. Modified Adolescent Stress Questionnaire (ASQ-I) was used to assess the stress in the students before and after the intervention. Results: The results indicate that performing YN was effective and significantly decreased the total stress (P < 0.001) and vital domains like the stress of home life (P < 0.005), school performance (P < 0.026), teacher interaction (P < 0.024), future uncertainty (P < 0.001), school and leisure conflict (P < 0.001). Also, at the end of the study in control, low and moderate stress was observed in 58.06% and 41.93%, while in the YN group, it was 96.15% and 3.85% and was statistically significant (p < 0.001). Conclusions: This study shows that YN effectively reduced psychosocial stress in adolescents and could be useful in school curriculum. Highlights: The current study aimed at understanding the usefulness of Yoga Nidra in mitigating stress mid (14–16 years) adolescents. The India-specific Adolescent stress Questionnaire (ASQ-I) that address stress of home life, school performance, attendance, peer pressure, body image, teacher interaction, future uncertainty, school or leisure conflict, financial pressure and emerging adult responsibility was used. Yoga Nidra effectively reduced psychosocial stress in adolescents and could be useful in school curriculum.